Structure in transition: The role of structure in facilitating workplace efficacy and belonging for military veterans and civilians - W. Connor Gibbs; Lauren Ortosky; Alair MacLean; Aaron C. Kay; David K. Sherman (PLoS ONE, 2025)
Employment transitions necessitate a degree of uncertainty and lack of control, which may present a challenge to succeeding and belonging at a new organization. The present research tests ideas derived from compensatory control theory which posits that people may seek external structure to help exert control over their lives when they experience a lack of control in an important life domain – and that this can aid in their goal pursuit. Across three studies, we explore whether the perception of a higher degree of organizational structure can help employees compensate for uncertainty and lack of control and facilitate transitioning employees’ occupation self-efficacy and sense of belonging in a new work environment. This research focuses on military veterans, who face significant challenges during their separation from military service and transition to civilian employment, as an exemplar of the people experiencing employment transitions more generally, and compares them (in two studies) with civilian participants. Across three studies, two using simple correlational methods, one using an experimental methodology with veterans and civilians, we find consistent evidence that when transitioning employees perceive greater structure at their organization, this facilitates increased feelings of occupational self-efficacy which, in turn, promotes greater feelings of belonging at work. When people perceive greater structure in their environment, people feel more efficacious and a greater sense that they belong at work. The results are discussed in the context of compensatory control theory, addressing the challenges of transitioning employees, and in particular, transitioning military veterans.